The effects of supplementary feeding of traditionally managed Bunaji cows - Otchere, E.O. (International Livestock Centre for Africa, 1986)
Describes effects of feeding Bunaji cows supplements of cottonseed cake, molasses-urea or fodder bank on birth & 1-year weight of calves and their viability to 1-year, and milk yield, for both calves & humans, of cows under an agropastoral management system.